Educating for Citizenship and Social Justice Practices for Community Engagement at Research Universities - Mitchell, Tania D.; Soria, Krista M. (Springer International Publishing : Imprint: Palgrave Macmillan, 2018)
XXIV, 314 p. 3 illus.